Effect Observation of Baduanjin Training on Chronic Nonspecific Low Back Pain - Feng GAO; Song YUAN; Na LIU; Shuji ZHENG (康复学报)
Objective:To observe the clinical curative effect of Baduanjin training in the therapy of chronic nonspecific low back pain.Methods:A total of 60 cases of chronic nonspecific low back pain were randomly divided into observation group and control group with 30 cases in each group. The control group only was treated by conventional rehabilitation therapy, the observation group was trained by Baduanjin practice on the basis of the control group. The patient's pain was assessed by Visual Analogue Scale (VAS), the patient's confidence in daily activities was assessed by the Pain Self-efficacy Questionnaire (PSEQ), the patient's anxiety and depression were assessed by the Hospital Anxiety and Depression Scale (HADS), the patient's functional status were assessed by the Oswestry Disability Index (ODI) before treatment and at the end of the treatment.Results:At the end of 8 weeks treatment, the VAS, HADS and ODI scores of the observation group and the control group were significantly lower than before treatment, the PSEQ was significantly higher than before the treatment, with statistically significant differences (P<0.05).Compared with the control group, the VAS, HADS, ODI scores of the observation group were significantly lower, the PSEQ scores in the observation group was more significant than that in the control group, with statistically significant differences (P<0.05).Conclusion:Baduanjin can effectively relieve pain in patients with chronic nonspecific low back pain, improve patients' self-efficacy, functional disorders, anxiety and depression with a disirable clinical curative effect.